Unusual excitation wavelength tunable multiple fluorescence from organocyclo-phosphazene microspheres: Crosslinked structure-property relationship. (17th December 2019) - Basharat, Majid; Abbas, Yasir; Liu, Wei; Ali, Zahid; Zhang, Shuangkun; Zou, Wenqi; Wu, Zhanpeng; Wu, Dezhen
Abstract: Herein, we reported the organocyclophosphazenes (OCP) microspheres with excitation wavelength tunable fluorescence (EWTF) emission by reacting hexachlorocyclotriphosphazene and 4, 4′-methylenedianiline via one-pot facile method. The as-prepared microspheres exhibit blue ( λ ex 280 nm), green ( λ ex 365/420 nm) and red ( λ ex 546 nm) tunable fluorescence emissions in the ultraviolet (UV) and visible region. The microspheres have shown broadband semiconductors like absorptions in UV and visible regions indicate the multiple bandgaps in the microspheres. The role of the crosslinked structure and property demonstrated that stable interactions are conceivable in microspheres than branched polymer, which imparted EWTF property. This study explored the cyclotriphosphazene as a platform for the synthesis of EWTF materials, and their potential utilization in the full spectrum tunable fluorescence and other light related technologies. Graphical abstract: Image 1 Highlights: A novel morphology controllable fluorescent microsphere based on CPs were synthesized. EWTF properties of the microspheres were achieved and the influence of crosslinked-structures was investigated. Mechanism of introducing non-conjugated structures attribute to multiple fluorescence emission due to crosslinking.